2015
DOI: 10.1027/1618-3169/a000298
|View full text |Cite
|
Sign up to set email alerts
|

Biased Processing of Ambiguous Symptoms Favors the Initially Leading Hypothesis in Sequential Diagnostic Reasoning

Abstract: In sequential diagnostic reasoning, observed pieces of evidence activate hypotheses in memory and are integrated to reach a final diagnosis. The order of evidence can influence diagnostic reasoning. This article examines the processing of ambiguous evidence underlying order effects if multiple hypotheses are activated. In five experiments with a quasi-medical scenario, participants dealt with symptom sequences supporting multiple diagnoses. The symptom order, the response mode (end-of-sequence, step-by-step), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 66 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, Rebitschek, Bocklisch, et al () showed how stepwise diagnostic reasoning partially counteracts the primacy effect and can even lead to a recency effect (see experiments 1B, 2B, and 3). Given this procedural influence, one could speculate that stepwise diagnostic reasoning may also counteract decoy effects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, Rebitschek, Bocklisch, et al () showed how stepwise diagnostic reasoning partially counteracts the primacy effect and can even lead to a recency effect (see experiments 1B, 2B, and 3). Given this procedural influence, one could speculate that stepwise diagnostic reasoning may also counteract decoy effects.…”
Section: Discussionmentioning
confidence: 94%
“…This hypothesis has also to be rejected. However, studies in diagnostic reasoning indicate that—depending on the presentation rate—both a primacy effect and a recency effect occur when the order of symptom presentation is varied (Lange, Thomas, Buttaccio, Illingworth, & Davelaar, ; Lange, Thomas, & Davelaar, ; Rebitschek, Bocklisch, et al, ). Nevertheless, there is also evidence for a recency effect in medical decision‐making (Bergus, Chapman, Levy, Ely, & Oppliger, ; Croskerry, ; Lawson & Daniel, ), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Larrick 42 suggests considering the opposite, as a way of avoiding confirmation bias and reducing overconfidence. Rebitschek and colleagues 36 found a reduction of the primacy effect when participants assessed each symptom in relation to each competing, potential cause. Educators could consider how such strategies can be formally and systematically introduced to the medical curricula.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, substantial evidence for predecisional information distortion in the literature, 29,30 which suggests that, as a judgment, hypothesis or preference emerges, information gets distorted to support it (either bolstered or denigrated or both), 3133 and that this happens with not only ambiguous but also diagnostic information. 34,35 In a series of experiments on diagnostic reasoning, in which students were taught the probabilistic relationships between fictitious chemicals and resulting health symptoms and were subsequently asked to identify the chemical that had caused the presenting symptoms, Rebitschek and colleagues 36 found a strong primacy effect: once an initial, leading hypothesis was established, it determined the final diagnosis, even in cases in which subsequent information was inconsistent. The authors attributed their findings to information distortion: participants changed the subjective value of the sequentially presented information to maintain coherence with their initial hypothesis, a phenomenon also supported by a number of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…1), adapted for the chemical accident paradigm (Jahn & Braatz, 2014;Meder & Mayrhofer, 2013;Mehlhorn, Taatgen, Lebiere, & Krems, 2011;Rebitschek, Bocklisch, Scholz, Krems, & Jahn, 2015). Participants were told that patients showing symptoms (effects) may have been affected by a chemical (root cause) because of an accident in a chemical plant.…”
Section: Experiments 1: Long Causal Chains and High Base Ratementioning
confidence: 99%